STUDENTS' PERCEPTIONS OF USING GOOGLE CLASSROOM DURING THE COVID-19 PANDEMIC - Annafi Annanda Oktaria; Laksmita Rahmayadevi (Universitas Ahmad Dahlan, 2021)
Technology has impacted most of the sectors, including the education field. Nowadays, many schools have incorporated technology through Information and Communication Technologies (ICT) into learning. This research investigates students' perception of Google Classroom as a learning tool during the covid-19 pandemic. The method used in this research is quantitative descriptive through an online questionnaire and online deep interview sessions with students from SMP Muhammadiyah Yogyakarta. Twenty-eight students have been joining Google Classroom in English learning for at least one term during the covid-19 pandemic. Five students were also interviewed to seek more information about their experiences using Google Classroom. Findings showed that several factors influence the students' online learning process in a covid-19 pandemic, namely, usefulness, ease of use, ease of learning, and satisfaction. In general, Google Classroom is very useful in improving students' skills, abilities, discipline, and independent learning through teaching materials.